Changes of ground vegetation, soil chemical properties and microbiota following the surface fires in Scots pine forests - Marozas, Vitas; Armolaitis, Kęstutis; Aleinikovienė, Jūratė (Journal of Environmental Engineering and Landscape Management, 2013)
The aim of the study was to investigate the influence of low severity surface fires on the ground vegetation, soil chemical changes and soil microbiota in Scots pine stands on sandy soils (Arenosols). The study was conducted in the eastern part of Lithuania (55° 35′N, 26° 07′E). The annual investigations in 1–4-year-old burned sites showed that low severity surface fires mostly affected the above-ground part of the ground vegetation. The influence of surface fire on soil chemical properties and soil microbiota was minor. Only slight increases in pH and in the content of total N in soil organic layer were detected. Concentrations of mobile K2O and heavy metals (Cd, Cr, Cu, Mn, Zn and Fe) slightly increased in the mineral topsoil. The actinobacteria abundance increased in the soil organic layer and the mineral topsoil of the burned sites. The abundance of micromycetes decreased in the mineral topsoil after the surface fires.First published online: 14 Dec 2012